Combined GSTT1 Null, GSTM1 Null and XPD Lys/Lys Genetic Polymorphisms and Their Association with Increased Risk of Chronic Myeloid Leukemia - Abdalhabib EK; Jackson DE; Alzahrani B; Elfaki EM; Hamza A; Alanazi F; Ali EI; Algarni A; Ibrahim IK; Saboor M (Dove Medical Press, 2021)
Ezeldine K Abdalhabib,1 Denise E Jackson,2 Badr Alzahrani,1 Elyasa M Elfaki,1 Alneil Hamza,1 Fehaid Alanazi,1 Elryah I Ali,3 Abdulrahman Algarni,3 Ibrahim Khider Ibrahim,4 Muhammad Saboor5,6 1Department of Clinical Laboratory Sciences, College of Applied Medical Sciences-Al Qurayyat, Jouf University, Sakaka, Saudi Arabia; 2Thrombosis and Vascular Diseases Laboratory, School of Health and Biomedical Sciences, RMIT University, Victoria, Australia; 3Department of Medical Laboratory Technology, College of Applied Medical Sciences, Northern Border University, Arar, Saudi Arabia; 4Department of Hematology, Faculty of Medical Laboratory Sciences, Al Neelain University, Khartoum, Sudan; 5Department of Medical Laboratory Technology, Faculty of Applied Medical Sciences, Jazan University, Jazan, Saudi Arabia; 6Medical Research Center (MRC), Jazan University, Jazan, Saudi ArabiaCorrespondence: Muhammad SaboorDepartment of Medical Laboratory Technology, Faculty of Applied Medical Science, Jazan University, Jazan, Saudi ArabiaTel +966 54 495 9029Email msaboor@jazanu.edu.saPurpose: Glutathione S-transferases (GSTT1 and GSTM1) are instrumental in detoxification process of activated carcinogens. Nucleotide excision repair is carried out by DNA helicase encoded by xeroderma pigmentosum group D (XPD) genes and aberrations in the XPD gene predisposes to increased risk of cancer. The present study aimed to investigate GSTT1, GSTM1 and XPD polymorphisms in newly diagnosed chronic myeloid leukemia (CML) patients and to examine the association of these polymorphisms with the risk of developing CML.Patients and Methods: This case-control study was carried out from June 2019 to August 2021 involving 150 newly diagnosed patients with CML and an equal number of randomly selected age- and sex-matched healthy individuals. A multiplex-PCR assay was used to genotype GSTT1 null and GSTM1 null polymorphisms. XPD gene polymorphism was detected by PCR-RFLP using predesigned gene-specific primers.Results: GSTT1 and GSTM1 null polymorphisms were detected in 42.7% and 61.3% of cases, respectively, compared to 18% and 35.3% for controls. The combination of both GST null polymorphisms revealed a significant association with CML. Frequencies of XPD Lys751Gln genotypes in cases were 62.7% heterozygous Lys/Gln, 24% homozygous Lys/Lys and 13.3% homozygous Gln/Gln, while in the controls were 74.7%, 20%, and 5.3%, respectively. Significant differences were also noted regarding the combination of GSTT1/GSTM1 null with XPD Lys/Lys, and GSTM1 null with XPD Lys/Lys.Conclusion: In conclusion, GSTT1 null, GSTM1 null and XPD polymorphisms showed positive association with the risk of development of CML. Furthermore, age and gender did not exhibit any association with the studied polymorphisms, while CML phases were associated with GSTT1 null polymorphism.Keywords: GSTT1 null polymorphism, GSTM1, XPD, chronic myeloid leukemia